Onset of fast magnetic reconnection and particle energization in laboratory and space plasmas. (1st December 2020) - Pucci, F.; Velli, M.; Shi, C.; Singh, K. A. P.; Tenerani, A.; Alladio, F.; Ambrosino, F.; Buratti, P.; Fox, W.; Jara-Almonte, J.; Ji, H.; Yamada, M.; et al.
Abstract : The onset of magnetic reconnection in space, astrophysical and laboratory plasmas is reviewed discussing results from theory, numerical simulations and observations. After a brief introduction on magnetic reconnection and approach to the question of onset, we first discuss recent theoretical models and numerical simulations, followed by observations of reconnection and its effects in space and astrophysical plasmas from satellites and ground-based detectors, as well as measurements of reconnection in laboratory plasma experiments. Mechanisms allowing reconnection spanning from collisional resistivity to kinetic effects as well as partial ionization are described, providing a description valid over a wide range of plasma parameters, and therefore applicable in principle to many different astrophysical and laboratory environments. Finally, we summarize the implications of reconnection onset physics for plasma dynamics throughout the Universe and illustrate how capturing the dynamics correctly is important to understanding particle acceleration. The goal of this review is to give a view on the present status of this topic and future interesting investigations, offering a unified approach.